Instability of PVDF Binder in the LiFePO4versus Li4Ti5O12 Li‐Ion Battery Cell. Issue 1 (15th December 2020) - Leanza, Daniela; Vaz, C. A. F.; Novák, Petr; El Kazzi, Mario
Abstract: The conventional formulation of electrodes used in Li‐ion batteries consists of a mixture of three components: an active material, a conductive additive (carbon), and an organic binder. While the first encompasses a broad spectrum of chemistries, the carbon and the binder are often standard elements of the composite, with the latter being, in most of the cathode cases, the polyvinylidene fluoride (PVDF). The high (electro‐)chemical inertia spanning over a broad range of oxidative and reductive potentials gives grounds for this choice. Herein, we demonstrate, contrary to electrochemical expectations, that the PVDF is electrochemically unstable at relatively low potentials. We consider in this study the LiFePO4 (LFP) cathode cycled versus Li4 Ti5 O12 (LTO) anode as a representative low‐voltage battery cell system. The binder degradation process starts upon charge on the LFP electrode at 3.45 V vs . Li + /Li when the PVDF binder reacts with lithium and forms LiF. The latter does not precipitate on the LFP but migrates/diffuses towards the LTO counter‐electrode, following the Li‐ions' trajectory. X‐Ray photoelectron spectroscopy complemented with the high lateral resolution of X‐ray photoemission electron microscopy disclosed the formation of a thin layer of LiF homogenously distributed across the LTO electrode, which partially dissolves (or decomposes) upon discharge. The degradation of the PVDF and the deposition and dissolution (and/or decomposition) of the LiF layer continue over subsequent charge and discharge cycles. The process is augmented when the cycling temperature is increased to 80 °C. The results shown in this work are crucial to interpret electrochemical data, such as specific charge decay or impedance rise, and have relevance for all PVDF‐based electrodes, especially when employed in high‐voltage battery cells where the more extreme cycling conditions exacerbate electrode components' stability. Abstract :